Einbildungskraft, Phantasie and hikikomori. Reflections on the Extremes of Imagination - Giacomelli, Alberto (Aesthetica Preprint, 2023)
In the first paragraph of the paper, I aim to show the semantic richness and at the same time the ambiguity of the notion of imagination. I therefore try to show how the notion of imagination tends to be distinguished from that of fantasy. In the second section, I briefly reconstruct the characteristics of Einbildungskraft in Kantian reflection and compare them with the notions of Bildungskraft and Phantasie in the work of Jean Paul Richter. While for Kant, fantasy is mostly disconnected from sensible reality and thus proves to be an unreliable faculty from a gnoseological point of view, for Jean Paul Richter it represents the most fertile and creative cognitive faculty. This romantic conception of the Phantasie is taken up in aesthetic terms by the Schlegel brothers, who recognise in it the essential endowment of genius. The last paragraph of the paper focuses on the social and existential phenomenon of hikikomori. Japanese youths confined in their rooms and addicted to virtual reality seem to be the perfect example of imaginative decadence, yet I try to show how precisely the virtual and digital fields can provide an opportunity for imaginative and creative practice.